Shiga Toxin-Producing Escherichia coli Isolated from Bovine Mastitic Milk: Serogroups, Virulence Factors, and Antibiotic Resistance Properties. (19th November 2012) - Momtaz, Hassan; Safarpoor Dehkordi, Farhad; Taktaz, Taghi; Rezvani, Amir; Yarali, Sajad
Abstract : The aim of this study was to detect the virulence factors, serogroups, and antibiotic resistance properties of Shiga toxin-producing Escherichia coli, by using 268 bovine mastitic milk samples which were diagnosed using California Mastitis Test. After E. coli identification, PCR assays were developed for detection of different virulence genes, serogroups, and antibiotic resistance genes of Escherichia coli . The antibiotic resistance pattern was studied using disk diffusion method. Out of 268 samples, 73 (27.23%) were positive for Escherichia coli, and, out of 73 positive samples, 15 (20.54%) were O26 and 11 (15.06%) were O157 so they were the highest while O111 was not detected in any sample so it was the lowest serogroup. Out of 73 STEC strains, 11 (15.06%) and 36 (49.31%) were EHEC and AEEC, respectively. All of the EHEC strains had stx1, eaeA, and ehly, virulence genes, while in AEEC strains stx1 had the highest prevalence (77.77%), followed by eaeA (55.55%). Totally, aadA1 (65.95%) had the highest while blaSHV (6.38%) had the lowest prevalence of antibiotic resistance genes. The disk diffusion method showed that the STEC strains had the highest resistance to penicillin (100%), followed by tetracycline (57.44%), while resistance to cephalothin (6.38%) was the lowest.